NEGOTIATING TRADITION AND MODERNITY: THE DIALECTICS OF CONSERVATISM AND PROGRESSIVISM IN TEMBANG SUNDA CIANJURAN - Budiman, Arif (Jurnal Kajian Seni, 2025)
Innovation in traditional arts often triggers polemics between conservative and progressive values. This study offers a dialectical model of innovation-response in traditional arts by using Tembang Sunda Cianjuran as a case study to integrate Lewis A. Coser’s functional conflict theory. Employing a qualitative methodology that combines case study and autoethnography, data were gathered through in-depth interviews, participant observation, and documentary analysis. This multi-method approach allowed for a comprehensive understanding of both the artistic negotiation process and the underlying community dynamics. The research found that (1) the innovation of "Nyiar Luang Tina Cianjuran" successfully addressed contemporary social issues without eliminating core aesthetic rules such as dongkari, laras (tuning), wanda (style), song, and lyrics; (2) thematic modernisation and multimedia integration significantly enhance the appeal to the younger generation; and (3) the conflict between conservatism and progressivism, when managed effectively, can foster internal cohesion and create harmony within traditional arts. This research concludes that responsible innovation can enrich cultural relevance without compromising traditional values.